2022
DOI: 10.3390/su14127273
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Parking Lot Pavements to Counteract Urban Heat Islands

Abstract: Urban heat islands (UHI) are one of the unequivocal effects of the ongoing process of climate change: anthropized areas suffer extreme heat events that affect the human perception of comfort. This study investigated the effects of road pavements as a passive countermeasure by comparing the air temperature (AT) and the predicted mean vote (PMV) for different surface materials used to pave a historical square in Rome, Italy. The software ENVI-met has been used to compare, for the whole year 2021, the performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…The currently most accredited hypothesis explains blistering with the following theory: during scorching summer days, exposure to solar radiation leads to high surface temperature values [55]. High air temperatures contribute to such conditions because the cooling capacity of the air is reduced.…”
Section: Inside Overpressurementioning
confidence: 99%
“…The currently most accredited hypothesis explains blistering with the following theory: during scorching summer days, exposure to solar radiation leads to high surface temperature values [55]. High air temperatures contribute to such conditions because the cooling capacity of the air is reduced.…”
Section: Inside Overpressurementioning
confidence: 99%
“…According to the Italian standard for the promotion of the minimum environmental criteria (CAM) [ 37 ], this study investigates a sustainable layout to improve the microclimate conditions of an existing square in Italy and answer the current efforts in energy transition [ 38 ]. In previous studies, the authors investigated San Pietro in Vincula Square, in the historic centre of Rome, and demonstrated the effectiveness of cool pavements in terms of AT reduction and the well-being perceived by citizens [ 39 , 40 ]. In particular, the most recent research [ 41 ] proved that concrete pavers, surrounding greenery, and trees imply significant mitigation of UHI with an AT reduction higher than 3 °C, half MRT value, and a maximum PMV value equal to 2.2.…”
Section: Introductionmentioning
confidence: 99%
“…The study area is St. Peter in Chains' square, in the historic center of Rome. In [38,39], the authors carried out microclimatic analyses in the same area and demonstrated the effectiveness of some different cool pavements in terms of PMV and AT values throughout the year. Due to urban planning restrictions and landscaping which constrain the design choices, light concrete slabs or a total grass layer in the parking area gave the best results, suggesting that an even greater UHI mitigation can be obtained by combining these two solutions, and the mechanical good performances of the modular pavements cannot be overlooked [40,41].…”
Section: Introductionmentioning
confidence: 99%